NaCl treatment on physio-biochemical metabolism and phenolics accumulation in barley seedlings. (30th November 2020) - Wang, Mian; Ding, Yuxuan; Wang, Qiaoe; Wang, Pei; Han, Yongbin; Gu, Zhenxin; Yang, Runqiang
Highlights: Low concentration NaCl promotes growth and nutritional quality of barley seedlings. The 10 mM NaCl treated barley seedlings exhibited higher antioxidant capacity. The 10 mM NaCl enhanced the biosynthesis of phenolic acids and flavonoids. NaCl stimulated the gene, protein expression and enzymes activity level. Abstract: Phenolics are important secondary metabolites in plants with strong antioxidant effects. Seeds germination and exogenous stimulation could activate endogenous enzymes to enhance the content of phenolic acids and flavonoids. Barley seeds geminated under NaCl (1–20 mM) treatment to evaluate the accumulation of phenolics in this study. Results showed that NaCl treatment significantly enhanced the growth of seedlings, especially bud length. NaCl treatment up-regulated genes and proteins expression of phenylalanine ammonia lyase (PAL), cinnamate-4-hydroxylase (C4H) and 4-coumarate-CoA ligase (4CL), resulting in the enhancement of their activities. As a result, phenolic acids and flavonoids contents increased by 11.19% and 32.54%, respectively, in which gallic acid, protocatechuic, fisetin, myricetin and quercetin were affected mostly. Moreover, NaCl treatment enhanced 2, 2′-azino-bis(3-ethylbenzothiazoline-6-sulfonic acid) (ABTS) and 1, 1-diphenyl-2-picrylhydrazyl (DPPH) free radical scavenging capacity. Hence, NaCl stimulated the synthesis of phenolic components via enhancing gene, protein expression and the activity of key enzymes.